Front Cover: Reversible C=C Bond Activation by an Intramolecularly Coordinated Antimony(I) Compound (Chem. Eur. J. 56/2019). Issue 56 (28th August 2019) - Kořenková, Monika; Hejda, Martin; Erben, Milan; Jirásko, Robert; Jambor, Roman; Růžička, Aleš; Rychagova, Elena; Ketkov, Sergey; Dostál, Libor
Abstract : An antimony(I) compound reversibly activates a C=C double bond. As illustrated by the Sb‐trampoline, the pincer‐ligand‐supported stibinidene is able to bind maleimides through their C=C bond and release them in solution in a dynamic equilibrium. The whole process formally relies on a well‐defined Sb I –Sb III redox couple that is assisted by the ligand's arms. This system, thus, exhibits a transition‐metal‐like reactivity, a feature that has not been described for other heavier pnictinidenes before. More information can be found in the Communication by S. Ketkov, L. Dostál et al. on page 12884 .